Pengaruh Bentuk dan Fluktuasi Ukuran Dot terhadap Pelebaran Garis Spektral Inhomogen pada Quantum Dot Gallium Nitrida (QD GaN) - Fitri Suryani Arsyad; Budi Mulyanti; Amiruddin Supu; Moehamad Barmawi (Jurnal Matematika & Sains, 2007)
Theoretical analysis of the phenomena of the size fluctuation in Gallium Nitride quantum dot (GaN QD) is presented inthis paper. The effect of QD size fluctuation on the electron and hole energy level and the inhomogeneous linebroadening is studied. Analytical expressions for the inhomogeneous line broadening are derived for a Gaussian sizefluctuation distribution. Decreasing in the QD carrier energy level is observed when QD size increases. The peak ofoptical transition energy probability (Emax) is shifted to higher energy when dot size fluctuation (ÏL) increases. Theoptical transition energy distribution (fE) of cylindrical QD is at the higher energy with the inhomogeneous linebroadening (ÏE) wider than those of conical, ellipsoidal, as well as semi ellipsoidal QD.